Defining the mechanistic binding of viral particles to a multi‐modal anion exchange resin. (5th July 2018) - Brown, Matthew R.; Burnham, Michael S.; Lute, Scott C.; Johnson, Sarah A.; Walsh, Alison A.; Brorson, Kurt A.; Roush, David J.
Abstract : A multi‐tiered approach to determine the binding mechanism of viral clearance utilizing a multi‐modal anion exchange resin was applied to a panel of four viral species that are typically used in validating viral clearance studies (i.e., X‐MuLV, MVM, REO3, and PrV). First, virus spiked buffer‐only experiments were conducted to evaluate the virus's affinity for single mode and multi‐modal chromatography resins under different buffer conditions in a chromatography column setting. From these results we hypothesize that the mechanisms of binding of the viruses involve binding to both the hydrophobic and anionic functional groups. This mechanistic view agreed with the general surface characteristics of the different virus species in terms of isoelectric point and relative hydrophobicity values. This hypothesized mechanistic binding was then tested with commercially relevant, in‐process materials, in which competitive binding occurred between the load components (e.g., viruses, target product, and impurities) and the resin. © 2018 American Institute of Chemical Engineers Biotechnol. Prog., 34:1019–1026, 2018